Advanced Congestive Heart Failure Associated With Disseminated Intravascular Coagulopathy - Annahita Sarcon MS, MD; Xiaoli Liu MD; David Ton MD; James Haywood MD; Todd Hitchcock MD (SAGE Publishing, 2015)
Background . Disseminated intravascular coagulopathy (DIC) is a complication of an underlying disease and not a primary illness. It is most commonly associated with sepsis, trauma, obstetrical complications, and malignancies. There are very few cases in the literature illustrating the association between DIC and congestive heart failure. Findings . In this report, we present a case of severe congestive heart failure, leading to biventricular thrombi and subsequently DIC. Conclusion . We suggest that the association between congestive heart failure and DIC is an underrecognized one. Congestive heart failure continues to remain a major cause of morbidity and mortality despite advances in medical therapies. Thus far, the precise role of coagulation factors in congestive heart failure is unknown. Further investigations are needed to elucidate the pathophysiology of congestive heart failure and coagulation factors.